The subjective scope of crime and its signs in criminal law - I.A. Tarkhanov; R.R. Gayfutdinov (Ученые записки Казанского университета: Серия Гуманитарные науки)
A general doctrine of the subjective scope of crime, the most difficult one for perception, was discussed. The rules were proposed for deciding on the form of guilt inherent in a particular type of crime if no such regulations can be found in the current criminal law. For this purpose, the special part of the Criminal Code of the Russian Federation was analyzed. Particular attention was paid to legislative innovations – for example, to the applicability of Pt. 2 of Art. 24 of the Criminal Code of the Russian Federation (with analysis, including the retrospective one), as well as to the new concept of elements of crime in “Violation of the requirements in the field of transport safety” (Art. 2631). It was concluded that no single rule can be found for defining the form of guilt as provided by Pt. 2 of Art. 24 of the Criminal Code of the Russian Federation, which negatively affects both interpretation of the law and its legal application.